Исследование возможности динамического и экономичного управления трансмиссией БТР-4 с двигателем 3ТД-3А - Толстолуцкий, В. А. (НТУ "ХПИ", 2011)
Investigation of the gearshift and hydro transformer blocking influence at dynamic characteristics of the speed increasing and fuel economy of the BTR-4 was studded. Cardinal principles were discovered for increase efficiency of transmission control system of BTR-4 for different condition of usage.
Keywords: военная техника; экономия топлива; стиль вождения; управление транспортом; бронетранспортер; гидродинамический трансформатор; трансмиссия